Regulatory Mechanisms of Baicalin in Cardiovascular Diseases: A Review - Xin, Laiyun; Gao, Jialiang; Lin, Hongchen; Qu, Yi; Shang, Chang; Wang, Yuling; Lu, Yingdong; Cui, Xiangning (Frontiers in Pharmacology, 2020)
Cardiovascular disease is the leading cause of high morbidity and mortality worldwide,wnich emphasizes the urgent necessity to develop new pharmacotherapies.In eastern countries, traditional Chinese medicine Scutellaria baicalensis has been widely used clinically for thousands of years. Baicalin is one of the main active ingredients extracted from Chinese medicine Scutellaria baicalensis. Emerging evidences have established that baicalin improves chronic in flammation, immune imbalance, disturbance of lipid metabolism, apoptosis and oxidative stress and thereby offers beneficial roles against the initiation and progression of cardiovascular diseases such as atherosclerosis, hypertension, myocardial infarction and reperfusion, heart failure. In this review, we summarize the relevant mechanisms by which baicalin regulates cardiovascular disease in hope of revealing more possibilities of baicalin in caidiovascular disease prevention and/or therapy.